2021
DOI: 10.21037/qims-20-667
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging-guided microwave ablation for lung tumor: a case report

Abstract: Thoracoscopic surgery is considered to be the best treatment option for pulmonary lesions.However, for patients with clinical stage IIIA, surgery is not always feasible, due to a lack of sufficient lung function. Microwave ablation (MWA) is an appropriate, minimally invasive treatment option for these patients. In this case study, we present our initial experience with MWA guided by magnetic resonance imaging (MRI), in a patient with a lesion located in the right lower lobe. The patient was successfully ablate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Recent reports have featured open high-field systems that provide improved visualization of lesions <1 cm, bullae, and small vessels. 11,[20][21][22][23] Of interest is also the option to operate the closed-bore (70 cm wide, 145 cm long) 1.5 T Magnetom Aera (Siemens Healthineers, Erlangen, Germany) at 0.55 T (Fig. 1), which results in reduced image distortion by virtue of the field homogeneity of this system configuration (Fig.…”
Section: Currently Available Hardware For Mr-guided Thoracic Interven...mentioning
confidence: 99%
See 2 more Smart Citations
“…Recent reports have featured open high-field systems that provide improved visualization of lesions <1 cm, bullae, and small vessels. 11,[20][21][22][23] Of interest is also the option to operate the closed-bore (70 cm wide, 145 cm long) 1.5 T Magnetom Aera (Siemens Healthineers, Erlangen, Germany) at 0.55 T (Fig. 1), which results in reduced image distortion by virtue of the field homogeneity of this system configuration (Fig.…”
Section: Currently Available Hardware For Mr-guided Thoracic Interven...mentioning
confidence: 99%
“…21 Shen et al reported a single MR-guided MWA in a patient with a right lower lobe lung adenocarcinoma of unknown size using a 3.0 T system (Ingenia, Philips, Amsterdam, the Netherlands), the ECO-100A system (ECO Medical Instrument Co., Ltd. Nanjing, China) with a 16-G cooled ceramic antenna and local anesthesia. 22 No coil was specified. Before acquiring planning images with unspecified T2w sequences, the authors instructed the patient to hold their breath for 10 seconds at the end of normal expiration and emphasized the importance of coaching patients before the procedure.…”
Section: Mwamentioning
confidence: 99%
See 1 more Smart Citation
“…Over the years, MRI has gained significant momentum with the emergence of new imaging techniques such as multi-channel MRI, systems with strong gradients, and innovative pulse-train techniques for parallel imaging ( Puderbach et al, 2007 ). MRI brings many advantages, including arbitrary direction imaging and high tissue resolution, and can identify changes in the ablation zone during the entire process of ablation, which is useful for monitoring changes in the ablation region ( Li et al, 2017 ; Shono et al, 2020 ; Shen et al, 2021 ). However, few studies have assessed the clinical utility and economic value of MRI-guided MWA.…”
Section: Introductionmentioning
confidence: 99%
“…Radiofrequency ablation (RFA) is a minimally invasive treatment based on alternating high-frequency electrical currents from an electrode that produces ionic agitation and generates frictional heat, thus causing coagulation necrosis [25][26][27]. In human medicine, the efficacy of RFA has been reported in several primary tumors and metastases, with improvements in the mass effect as well as controlling the biological activity of the tumor [28][29][30][31][32][33][34][35][36][37][38][39][40][41]. In veterinary medicine, percutaneous ultrasound-guided RFA has been used successfully to treat functioning parathyroid and thyroid masses in dogs [42][43][44][45] and cats [46], respectively.…”
Section: Introductionmentioning
confidence: 99%